Estudo do teste SNHT (Standart Normal Homogeneity Test) para detecção de pontos de mudança em séries temporais - Chianezzi, Giovanna Garutti (Universidade Federal de São Carlos, 2021)
The study of time series is extremely important for a better understanding how certain events develop over time. To do this, be able to to indicate the exact moment when a given phenomenon changes its pattern of behavior is a very nice feature. This work goes deeper into the theme of detecting change points in series temporal through the use of the SNHT (Standard Normal Homogeneity Test), which consists of a statistical test proposed specifically for this purpose. Some basic statistical concepts and the test in are only explained in detail. The example of the test is performed by applying it to data about the number of drivers killed or seriously injured in traffic accidents in Great Britain. Brittany between the years 1969 - 1984. An experiment, from series of simulated moving averages, will be carried out for that it is possible to get a good sense of the power of the test and its performance. It is analysis will be done through the analysis of Type II Error rates obtained by SNHT. And to complete the study completely, the SNHT will be applied to data referring to the number of new cases of Covid-19 in the city of São Paulo, in an attempt to understand Covid-19's pandemic behavior during its first year.
Study of the SNHT test (Standart Normal Homogeneity Test) for detection of change points in time series
Keywords: Covid-19; Estatística; Ponto de mudança; Quebra estrutural; Séries temporais; SNHT; Teste de Hipóteses; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::PROBABILIDADE E ESTATISTICA APLICADAS